Does early socio-economic disadvantage predict comorbid alcohol and mental health disorders? - Salom, C.; Williams, G.; Najman, J.; Alati, Rosa (Elsevier Ireland Ltd, 2014)
Background: Alcohol and mental health disorders are highly prevalent in the general population, with co-occurrence recognised as a major public health issue. Socio-economic factors are frequently associated with both disorders but their temporal association is unclear. This paper examines the association between prenatal socio-economic disadvantage and comorbid alcohol and mental health disorders at young adulthood. Methods: An unselected cohort of women was enrolled during early pregnancy in the large longitudinal Mater-University of Queensland Study of Pregnancy (MUSP), at the Mater Misericordiae Public Hospital in Brisbane, Australia. The mothers and their offspring were followed over a 21 year period. Offspring from the MUSP birth cohort who provided full psychiatric information at age 21 and whose mothers provided socioeconomic information at baseline were included (n= 2399). Participants were grouped into no-disorder, mental health disorder only, alcohol disorder only or comorbid alcohol and mental health disorders according to DSM-IV diagnoses at age 21 as assessed by the Composite International Diagnostic Interview. We used multivariate logistic regression analysis to compare associations of disorder group with single measures of prenatal socio-economic disadvantage including family income, parental education and employment, and then created a cumulative scale of socioeconomic disadvantage. Results: Greater socio-economic disadvantage was more strongly associated with comorbidity (OR 3.36; CI951.37, 8.24) than with single disorders. This relationship was not fully accounted for by maternal mental health, smoking and drinking during pregnancy. Conclusion: Multiple domains of socio-economic disadvantage in early life are associated with comorbid alcohol and mental health disorders. © 2014 Elsevier Ireland Ltd.